The Relationship Between Loneliness And Self-Disclosures Among Students Using Instagram In Medan City - Dinda Gustari; Nancy Naomi Aritonang (Jurnal Ilmu Sosial dan Humaniora, 2025)
This study aims to determine the relationship between loneliness and self-disclosure in students who use Instagram in Medan City. This study uses a quantitative approach with descriptive analysis to describe the level of loneliness and self-disclosure in final year students. In this study, the sampling technique used is non-probability sampling through a purposive sampling method. Based on the results of research on the relationship between loneliness and self-disclosure in students who use Instagram in Medan City, it can be concluded as follows: There is no significant relationship between loneliness and self-disclosure in students who use Instagram in Medan City. This is evidenced by the Pearson correlation coefficient value of 0.092 and a significance level of 0.083 (p> 0.05). Thus, H0 is accepted and Ha is rejected, which means that the level of loneliness experienced by students is not significantly related to how often or how deeply they express themselves on Instagram. The level of loneliness of students is classified as moderate, namely 75.6%, with the most prominent aspect being personality which is in the high category in 50.8% of subjects. The level of self-disclosure of students is also classified as moderate, namely 57.0%, with the most prominent aspect being honesty which is in the high category in 33.7% of subjects